Proofs of trig identities

(Redirected from Trig identity proof)
Shortcut:

Introduction

$\sin$ and $\cos$ are easy to define. I prefer the unit circle definition as it makes these proofs easier to understand. Next, we define some other functions:

$\tan = \frac{\sin}{\cos}$

$\cot = \frac{\cos}{\sin}$

$\sec = \frac{1}{\cos}$

$\csc = \frac{1}{\sin}$

Note: I've omitted $\theta$ because it's unnecessary and might clog things up a little.

With a bit of ingenuity, we can create the following diagram:

[asy] import olympiad; markscalefactor = 1/96; real d = radians(40); unitsize(72); pair O = (0,0); draw(circle(O,1)); dot(O); label("O",O,dir(180+degrees(d)/2)); label("$\theta$",shift(dir(degrees(d)/2)/5)*O,dir(degrees(d)/2)); pair G = (0,1); label("G",G,N); pair A = (cos(d),0); label("A",A,S); pair B = (cos(d),sin(d)); label("B",B,dir(135+degrees(d))); pair C = (1,0); label("C",C,SE); pair D = (1,tan(d)); label("D",D,N); pair E = (1/tan(d),0); label("E",E,SE); pair F = (1/tan(d),1); label("F",F,N); pair G = (0,1); label("G",G,N); draw(D--O--C--D--B--A--E--F--G--O--F); draw(rightanglemark(G,O,C)); label("$\cos \theta$",O--A); label("$\sin \theta$",B--A); label("1",B--O); draw(shift(dir(270)/24)*brace(C,O)); label("$\cot \theta$",shift(dir(270)/4)*brace(E,O),S); draw(shift(dir(d+90)/24)*brace(O,D)); label("$\sec \theta$",shift(dir(degrees(d)+90)/24)*brace(O,D),dir(degrees(d)+90)); draw(shift(dir(270)/4)*brace(E,O)); label("1",shift(dir(270)/24)*brace(C,O),S); draw(shift(dir(270)/4)*O--shift(dir(270)/24)*O); draw(shift(dir(270)/4)*E--shift(dir(270)/24)*E); label("1",E--F,SE); label("$\tan \theta$",C--D); draw(shift(dir(degrees(d)+90)/4)*brace(O,F)); label("$\csc \theta$",shift(dir(degrees(d)+90)/4)*brace(O,F),dir(degrees(d)+90)); draw(shift(dir(degrees(d)+90)/4)*O--shift(dir(degrees(d)+90)/24)*O); draw(shift(dir(degrees(d)+90)/4)*F--shift(dir(degrees(d)+90)/24)*F); [/asy]

We can note that the functions are correct by similar triangles.

Back to Top

Symmetric identities

If we draw a few copies of the triangle, we get:

$\sin()=\cos(90-)=-\cos(90+)=\sin(180-)=-\sin(180+)=\cos(270-)=-\cos(270+)=-\sin(-)$

$\cos()=\sin(90-)=\sin(90+)=-\cos(180-)=-\cos(180+)=\sin(270-)=-\sin(270+)=\cos(-)$

$\tan()=\cot(90-)=-\cot(90+)=-\tan(180-)=\tan(180+)=\cot(270-)=-\cot(270+)=-\tan(-)$

The other three can be derived by taking the reciprocals of these three.

Back to Top

Pythagorean identities

Pythagorean identities are easy and there's no algebra involved. In fact, the name Pythagorean is a giveaway of what we should do!

$\cos^2+\sin^2=1$

The proof here is very straightforward. We use the pythagorean theorem on $\triangle OAB$ giving us $OA^2+AB^2=OB^2$ or $\sin^2+\cos^2=1^2$.

$\tan^2+1=\sec^2$

Same story here. Applying pythagorean to $\triangle OCD$ gives us $OC^2+CD^2=OD^2$ or $\tan^2+1^2=\sec^2$.

$1+\cot^2=\csc^2$

Same. Pythagorean on $\triangle OEF$ gives $OE^2+EF^2=OF^2$ or $1^2+\cot^2=\csc^2$.

Conclusion

Even though with the first one and the definitions, we can make the rest from algebra, having a geometric meaning is nice when we want to know what it actually means.

Back to Top

Angle addition and subtraction

[asy] unitsize(216); real d = 1/cos(radians(35)); real d1 = d * cos(radians(55)); real d2 = d * sin(radians(55)); pair O = (0,0); pair A = (cos(radians(20)),0); pair B = (cos(radians(20)),sin(radians(20))); pair C = (cos(radians(20)),d2); pair D = (d1,d2); draw(O--A--B--O--D--B--O--D--C--B); dot(O); dot(B); dot(A,red); dot(C,green); dot(D,blue); label("O",O,SW); label("$\alpha$",shift(dir(10)/5)*O); label("$\beta$",shift(dir(37.5)/5)*O); label("A",A,SE,red); label("B",B,E); label("C",C,NE,green); label("D",D,dir(122.5),blue); label("$\cos \alpha$",O--A,S); label("$\sin \alpha$",A--B,E); label("1",O--B,dir(302.5)); label("$\frac{\cos \alpha \sin \beta}{\cos \beta}$",B--C,E); label("$\frac{\sin \alpha \sin \beta}{\cos \beta}$",C--D,N); label("$\frac{\sin \beta}{\cos \beta}$",B--D,dir(200)); label("$\frac{1}{\cos \beta}$",D--O,dir(325)); [/asy]

where $\triangle OAB \sim \triangle BCD$

The diagram illustrates the identities nicely.

$\sin(\alpha + \beta)$

The diagram shows the height of point $D$ is $\sin(\alpha)+\frac{\cos \alpha \sin \beta}{\cos \beta}$. However, the length of $OD$ is $\frac{1}{\cos\beta}$. To compensate, we must divide by $\frac{1}{\cos\beta}$ to make it the sine. After some *easy* algebra, we arrive at $\sin(\alpha+\beta)=\sin\alpha\cos\beta+\sin\beta\cos\alpha$.

$\cos(\alpha + \beta)$

The diagram says that it is $\cos(\alpha)-\frac{\sin \alpha \sin \beta}{\cos \beta}$, but we need to divide by $\frac{1}{\cos\beta}$ again. We arrive at $\cos(\alpha+\beta)=\cos\alpha\cos\beta-\sin\alpha\sin\beta$.

$\tan(\alpha + \beta)$

This time we can't get it from our diagram. We need to go back to the original definition of tangent. This is the summary of my algebra: $\tan (\alpha + \beta ) = \frac{\sin (\alpha + \beta )}{\cos (\alpha + \beta )} = \frac{\sin \alpha \cos \beta + \cos \alpha \sin \beta}{\cos \alpha \cos \beta - \sin \alpha \sin \beta} = \frac{\frac{\sin \alpha \cos \beta + \cos \alpha \sin \beta}{\cos \alpha \cos \beta}}{\frac{\cos \alpha \cos \beta - \sin \alpha \sin \beta}{\cos \alpha \cos \beta}} = \frac{\frac{\sin \alpha}{\cos \alpha} + \frac{\sin \beta}{\cos \beta}}{1 - \frac{\sin \alpha \sin \beta}{\cos \alpha \cos \beta}} = \frac{\tan \alpha + \tan \beta}{1 - \tan \alpha \tan \beta}$

Back to Top

Double angle formulas

This is a breeze. Just sub in for sum:

$\sin(2)=2\sin\cos$

$\cos(2)=\cos^2-\sin^2$

$\tan(2)=\frac{2\tan}{1-\tan^2}$

Variations

Since $\sin^2+\cos^2=1$, we can edit the double angle cosine formula a bit. Here are the three most helpful variants:

$\cos(2)=2\cos^2-1$

$\cos(2)=\cos^2-\sin^2$

$\cos(2)=1-2\sin^2$

We can also solve for other expressions:

$\sin^2=\frac{1-\cos(2)}{2}$

$\cos^2=\frac{\cos(2)+1}{2}$

Back to Top

Sum to Product to Sum

Our angle addition formulas look nasty. Let's try to cancel something.

Chapter 1

Let's start with the formula $\sin(\alpha + \beta)=\sin\alpha\cos\beta+\sin\beta\cos\alpha$. Both terms are symmetrical, let's try to cancel out the first one.

$\sin()=-\sin(-)$ and $\cos() = \cos(-)$ might give us an idea. $\sin(\beta -\alpha)=-\sin\alpha\cos\beta+\sin\beta\cos\alpha$

Therefore, $\sin(\beta +\alpha)+\sin(\beta -\alpha)=\sin\alpha\cos\beta+\sin\beta\cos\alpha-\sin\alpha\cos\beta+\sin\beta\cos\alpha=2\sin\beta\cos\alpha$.

To put this in a nicer form, $2\sin\alpha\cos\beta\iff\sin\theta+\sin\phi$ where:

$\theta =\alpha +\beta$

$\phi =\alpha -\beta$

$\alpha =\frac{\theta +\phi}{2}$

$\beta =\frac{\theta -\phi}{2}$

Chapter 2

We did all we could. Now let's try doing something to the other formula: $\cos(\alpha + \beta)=\cos\alpha\cos\beta-\sin\alpha\sin\beta$. Let's try to cancel the first one first. $\sin$ is a lot easier to cancel than $\cos$ so we have to subtract.

$-\cos(\alpha -\beta)=-\cos\alpha\cos\beta-\sin\alpha\sin\beta$

So $\cos(\alpha+\beta)-\cos(\alpha-\beta)=-2\sin\alpha\sin\beta$

Or, $2\sin\alpha\sin\beta\iff\cos\phi-\cos\theta$ (same conversions of $\alpha,\beta\iff\theta,\phi$)

Chapter 3

Next: $\cos(\alpha + \beta)=\cos\alpha\cos\beta-\sin\alpha\sin\beta$. Now let's cancel the second one.

$\cos(\alpha -\beta)=\cos\alpha\cos\beta+\sin\alpha\sin\beta$

So $\cos(\alpha+\beta)+\cos(\alpha-\beta)=2\cos\alpha\cos\beta$

Or, $2\cos\alpha\cos\beta\iff\cos\theta+\cos\phi$ (same conversions of $\alpha,\beta\iff\theta,\phi$)

Back to Top

Bonus: Product identity

This is a special identity. I hope this helps you. $\sin^2(\alpha+\beta)=(\sin\alpha\cos\beta+\cos\alpha\sin\beta)(\sin\alpha\cos\beta+\cos\alpha\sin\beta)=\sin^2\alpha\cos^2\beta+\cos^2\alpha\sin^2\beta+2\sin\alpha\sin\beta\cos\alpha\cos\beta$

and

$\cos^2(\alpha+\beta)=(\cos\alpha\cos\beta-\sin\alpha\sin\beta)(\cos\alpha\cos\beta-\sin\alpha\sin\beta)=\sin^2\alpha\cos^2\beta+\cos^2\alpha\sin^2\beta+(\sin\alpha\cos\alpha)^2+(\sin\beta\cos\beta)^2$

There's something we can cancel.

$\cos(2\alpha+2\beta)=\cos^2(\alpha+\beta)-\sin^2(\alpha+\beta)$

$=(\sin\alpha\cos\alpha)^2+(\sin\beta\cos\beta)^2-2\sin\alpha\cos\alpha\sin\beta\cos\beta$

If $f()=\sin\cos$, then it simplifies to

$(f(\alpha)-f(\beta))^2$

Notice $f\left(\frac{k\pi}{2}\right)=0$. If we let $\beta=0$:

$\cos(2\alpha+k\pi)=\sin^2\alpha\cos^2\alpha$

Back to Top

Halved angles

Starting with the identities from the double section:

$\sin^2=\frac{1-\cos(2)}{2}$

$\cos^2=\frac{1+\cos(2)}{2}$

We take the square root to obtain:

$\sin=\pm\sqrt{\frac{1-\cos(2)}{2}}$

$\cos=\pm\sqrt{\frac{1+\cos(2)}{2}}$

For tangent:

$\tan=\frac{\sin}{\cos}=\frac{\pm\sqrt{\frac{1-\cos(2)}{2}}}{\pm\sqrt{\frac{1+\cos(2)}{2}}}=\pm\sqrt{\frac{1-\cos(2)}{1+\cos(2)}}$

There are two nice variations to know.

$\pm\sqrt{\frac{1-\cos(2)}{1+\cos(2)}}\times\sqrt{\frac{1-\cos(2)}{1-\cos(2)}}=\pm\frac{1-\cos(2)}{\sin(2)}$

$\pm\sqrt{\frac{1-\cos(2)}{1+\cos(2)}}\times\sqrt{\frac{1+\cos(2)}{1+\cos(2)}}=\pm\frac{\sin(2)}{1+\cos(2)}$

Back to Top

Triple angles and more

Triple sums

$\sin(\alpha+\beta+\gamma)=\sin(\alpha+(\beta+\gamma))$ $=\sin\alpha\cos(\beta+\gamma)+\cos\alpha\sin(\beta+\gamma)$ $=\sin\alpha(\cos\beta\cos\gamma-\sin\beta\sin\gamma)+\cos\alpha(\sin\beta\cos\gamma+\cos\beta\sin\gamma)$ $=\sin\alpha\cos\beta\cos\gamma+\cos\alpha\sin\beta\cos\gamma+\cos\alpha\cos\beta\sin\gamma-\sin\alpha\sin\beta\sin\gamma$

$\cos(\alpha+\beta+\gamma)=\cos(\alpha+(\beta+\gamma))$ $=\cos\alpha\cos(\beta+\gamma)-\sin\alpha\sin(\beta+\gamma)$ $=\cos\alpha(\cos\beta\cos\gamma-\sin\beta\sin\gamma)-\sin\alpha(\sin\beta\cos\gamma+\cos\beta\sin\gamma)$ $=\cos\alpha\cos\beta\cos\gamma-\cos\alpha\sin\beta\sin\gamma-\sin\alpha\cos\beta\sin\gamma-\sin\alpha\sin\beta\cos\gamma$

$\tan(\alpha+\beta+\gamma)=\tan(\alpha+(\beta+\gamma))$ $=\frac{\tan\alpha+\tan(\beta+\gamma)}{1-\tan\alpha\tan(\beta+\gamma)}$ $=\frac{\tan\alpha+\frac{\tan\beta+\tan\gamma}{1-\tan\beta\tan\gamma}}{1-\tan\alpha\frac{\tan\beta+\tan\gamma}{1-\tan\beta\tan\gamma}}$ $=\frac{\frac{\tan\alpha+\tan\beta+\tan\gamma-\tan\alpha\tan\beta\tan\gamma}{1-\tan\beta\tan\gamma}}{\frac{1-\tan\beta\tan\gamma-\tan\alpha\tan\beta-\tan\alpha\tan\gamma}{1-\tan\beta\tan\gamma}}$ $=\frac{\tan\alpha+\tan\beta+\tan\gamma-\tan\alpha\tan\beta\tan\gamma}{1-\tan\beta\tan\gamma-\tan\alpha\tan\gamma-\tan\alpha\tan\beta}$

Triple angles

$\sin 3\theta=3\cos^2\theta\sin\theta-\sin^3\theta=3\sin\theta-3(1-\cos^2\theta)\sin\theta-\sin^3\theta=3\sin\theta-4\sin^3\theta$

$\cos 3\theta=\cos^3\theta-3\cos\theta\sin^2\theta=\cos^3\theta+3(1-\sin^2\theta)\cos\theta-3\cos\theta=4\cos^3\theta-3\cos\theta$

$\tan 3\theta=\frac{3\tan\theta-\tan^3\theta}{1-3\tan^2\theta}$

Third angles

Let $\sin\theta = x$ and $\sin 3\theta = y$. We get this depressed cubic:

$0=3x-4x^3-y$

First, divide both sides by -4 and rearrange: $x^3-\frac{3}{4}x+y=0$. The discriminant $\Delta = \frac{y^2}{4}-\frac{1}{64}=\frac{16y^2-1}{64}$

Then, $u=\frac{-4y\pm\sqrt{16y^2-1}}{8}$

The solutions are $\sqrt[3]{-4y+\sqrt{16y^2-1}}$, $\frac{\sqrt[3]{-4y+\sqrt{16y^2-1}}+\sqrt[3]{4y-\sqrt{16y^2-1}}}{2}$, and $\sqrt[3]{-4y-\sqrt{16y^2-1}}$.

A tiny adjustment gives us the cosine third-angle formulas:

$\sqrt[3]{4y+\sqrt{16y^2-1}}$, $\frac{\sqrt[3]{4y+\sqrt{16y^2-1}}+\sqrt[3]{4y-\sqrt{16y^2-1}}}{2}$, and $\sqrt[3]{4y-\sqrt{16y^2-1}}$.

For tangent:

$\frac{\sqrt[3]{-4y+\sqrt{16y^2-1}}}{\sqrt[3]{4y+\sqrt{16y^2-1}}}$, $\frac{\sqrt[3]{-4y+\sqrt{16y^2-1}}+\sqrt[3]{-4y-\sqrt{16y^2-1}}}{\sqrt[3]{4y+\sqrt{16y^2-1}}+\sqrt[3]{4y-\sqrt{16y^2-1}}}$, and $\frac{\sqrt[3]{-4y-\sqrt{16y^2-1}}}{\sqrt[3]{4y-\sqrt{16y^2-1}}}$

Back to Top

All identities

Definition

$\tan = \frac{\sin}{\cos}$

$\cot = \frac{\cos}{\sin}$

$\sec = \frac{1}{\cos}$

$\csc = \frac{1}{\sin}$

Symmetric

$\sin(x)=\cos(90-x)=-\cos(90+x)=\sin(180-x)=-\sin(180+x)=\cos(270-x)=-\cos(270+x)=-\sin(-x)$

$\cos(x)=\sin(90-x)=\sin(90+x)=-\cos(180-x)=-\cos(180+x)=\sin(270-x)=-\sin(270+x)=\cos(-x)$

$\tan(x)=\cot(90-x)=-\cot(90+x)=-\tan(180-x)=\tan(180+x)=\cot(270-x)=-\cot(270+x)=-\tan(-x)$

Pythagorean

$\cos^2+\sin^2=1$

$\tan^2+1=\sec^2$

$1+\cot^2=\csc^2$

Sum

$\sin(\alpha+\beta)=\sin\alpha\cos\beta+\sin\beta\cos\alpha$

$\cos(\alpha+\beta)=\cos\alpha\cos\beta-\sin\alpha\sin\beta$

$\tan(\alpha + \beta)=\frac{\tan \alpha + \tan \beta}{1 - \tan \alpha \tan \beta}$

Double

$\sin(2n)=2\sin n\cos n$

$\cos(2n)=\cos^2 n-\sin^2 n$

$\tan(2n)=\frac{2\tan n}{1-\tan^2 n}$

$\cos(2n)=2\cos^2 n-1$

$\cos(2n)=\cos^2 n-\sin^2 n$

$\cos(2n)=1-2\sin^2 n$

Sum $\iff$ Product

$\theta =\alpha +\beta$

$\phi =\alpha -\beta$

$\alpha =\frac{\theta +\phi}{2}$

$\beta =\frac{\theta -\phi}{2}$

$2\sin\alpha\cos\beta\iff\sin\theta+\sin\phi$

$2\sin\alpha\sin\beta\iff\cos\phi-\cos\theta$

$2\cos\alpha\cos\beta\iff\cos\theta+\cos\phi$

Product

$\cos(2\alpha+k\pi)=\sin^2\alpha\cos^2\alpha$

Halves

$\sin\theta=\pm\sqrt{\frac{1-\cos(2\theta)}{2}}$

$\cos\theta=\pm\sqrt{\frac{1+\cos(2\theta)}{2}}$

$\tan\theta=\pm\sqrt{\frac{1-\cos(2\theta)}{1+\cos(2\theta)}}$

$\tan\theta=\pm\frac{1-\cos(2\theta)}{\sin 2\theta}$

$\tan\theta=\pm\frac{\sin 2\theta}{1+\cos(2\theta)}$

3 Sums

$\sin(\alpha+\beta+\gamma)=\sin\alpha\cos\beta\cos\gamma+\cos\alpha\sin\beta\cos\gamma+\cos\alpha\cos\beta\sin\gamma-\sin\alpha\sin\beta\sin\gamma$

$\cos(\alpha+\beta+\gamma)=\cos\alpha\cos\beta\cos\gamma-\cos\alpha\sin\beta\sin\gamma-\sin\alpha\cos\beta\sin\gamma-\sin\alpha\sin\beta\cos\gamma$

$\tan(\alpha+\beta+\gamma)=\frac{\tan\alpha+\tan\beta+\tan\gamma-\tan\alpha\tan\beta\tan\gamma}{1-\tan\beta\tan\gamma-\tan\alpha\tan\gamma-\tan\alpha\tan\beta}$

Triple

$\sin 3\theta=3\sin\theta-4\sin^3\theta$

$\cos 3\theta=4\cos^3\theta-3\cos\theta$

$\tan 3\theta=\frac{3\tan\theta-\tan^3\theta}{1-3\tan^2\theta}$

Thirds

$\sin\theta=\sqrt[3]{-4\sin 3\theta+\sqrt{16\sin^2(3\theta)-1}},\frac{\sqrt[3]{-4\sin 3\theta+\sqrt{16\sin^2(3\theta)-1}}+\sqrt[3]{-4\sin 3\theta-\sqrt{16\sin^2(3\theta)-1}}}{2}, \\ \text{or }\sqrt[3]{4\sin 3\theta-\sqrt{16\sin^2 3\theta-1}}$

$\cos\theta=\sqrt[3]{4\cos 3\theta+\sqrt{16\cos^2(3\theta)-1}},\frac{\sqrt[3]{4\cos 3\theta+\sqrt{16\cos^2(3\theta)-1}}+\sqrt[3]{4\cos 3\theta-\sqrt{16\cos^2(3\theta)-1}}}{2}, \\ \text{or }\sqrt[3]{4\cos 3\theta-\sqrt{16\cos^2 3\theta-1}}$

$\tan\theta=\frac{\sqrt[3]{-4\sin 3\theta+\sqrt{16\sin^2(3\theta)-1}}}{\sqrt[3]{4\cos 3\theta+\sqrt{16\cos^2(3\theta)-1}}},\frac{\sqrt[3]{-4\sin 3\theta+\sqrt{16\sin^2(3\theta)-1}}+\sqrt[3]{-4\sin 3\theta-\sqrt{16\sin^2(3\theta)-1}}}{\sqrt[3]{4\cos 3\theta+\sqrt{16\cos^2(3\theta)-1}}+\sqrt[3]{4\cos 3\theta-\sqrt{16\cos^2(3\theta)-1}}}, \\ \text{or }\frac{\sqrt[3]{-4\sin 3\theta-\sqrt{16\sin(3\theta)^2-1}}}{\sqrt[3]{4\cos 3\theta-\sqrt{16\cos^2(3\theta)-1}}}$

See also

Trigonometric identities

Created by Afly (talk)

Back to Top